Breakage behavior of two different coal types in a grinding process and importance for thermal power stations. (17th February 2018) - Samanli, S.
ABSTRACT: This study investigates the effect of changes in coal properties in thermal power plants (TPPs) due to the breakage behavior of coal in the grinding stage. A grinding process is carried out in a stirred mill for different periods of time to determine the specific breakage rate. Two different types of coal with different properties and similar calorific values are used to compare their breakage rates. The results of the stirred mill grinding are presented in a comparative manner. Furthermore, washing tests are performed on the coal to determine the solid fossil fuel structure. It is shown that the solid fossil fuel structure affects linear and non-linear movement that results in different breakage behaviors.